2015
DOI: 10.3389/fpsyg.2015.00705
|View full text |Cite
|
Sign up to set email alerts
|

First-born siblings show better second language skills than later born siblings

Abstract: We examined the extent to which three sibling structure variables number of siblings, birth order, and presence of an older sibling at school age are linked to the second language skills of bilingual children. The research questions were tested using an ethnically heterogeneous sample of 1209 bilingual children with German as a second language. Controlling for children’s age, sex, nationality, number of children’s books at home, family language and parental German language skills, hierarchical regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Therefore, future research may benefit from reliance on representative samples, and should preferably be conducted in other cultural contexts with different sample types to test the generalizability of our obtained results. Optimally, such future scholarly work should also measure and control for further confounding factors that may influence sibling dynamics (Keller et al, 2015;Grønhøj, 2016;Halder et al, 2020;Hou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future research may benefit from reliance on representative samples, and should preferably be conducted in other cultural contexts with different sample types to test the generalizability of our obtained results. Optimally, such future scholarly work should also measure and control for further confounding factors that may influence sibling dynamics (Keller et al, 2015;Grønhøj, 2016;Halder et al, 2020;Hou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have demonstrated that first-born children have an advantage in educational attainment, health status and later outcomes in life over their later-born counterparts (Behrman and Taubman 1986;Hanushek 1992;Price 2008;Keller et al 2015). Interestingly, when birth order is controlled for, family size has either a small effect or no effect on the first-born child (Black et al 2005;Conley and Glauber 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the impact of birth order on language development in monolingual children shows mixed results, with some studies suggesting first-born children have better language skills (e.g., Berglund et al 2005;Zyrianova and Chertkova 2011), while others find the reverse pattern (Oshima-Takane et al 1996), or no relation at all (Lu et al 2022). For bilingual children, birth order may influence language input, with older siblings potentially playing a significant role (Keller et al 2015), providing more advanced language input compared to mothers (Bergroth and Palviainen 2016).…”
Section: Birth Ordermentioning
confidence: 99%